Pengaruh Kompres Jahe Merah terhadap Penurunan Skala Nyeri pada Lansia Penderita Gout Arthritis Dikelurahan Dataran Tinggi Binjai - Ade Irma Triana Siregar; Katini Katini; Christanti Rointan Br. Simatupang (Lembaga Pengembangan Kinerja Dosen, 2025)
Gout Arthritis is a non-communicable disease that occurs due to the accumulation of crystals in the joints, resulting in increased levels of uric acid in the body, and can attack joints, especially the joints of the heels, knees, toes and in the hands such as wrists, fingers and elbows. Common complaints are pain, swelling, inflammation, heat, stiffness and even unable to do activities as usual (Nurhayati, 2018) 1. To determine the effect of red ginger compresses on reducing the pain scale in patients with Gout Arthritis. This study uses a One-group pretest-posttest design research design approach. The sample of this study was 4 respondents. The sampling technique uses the Purpose formula. The collection of research data uses demographic data, consent sheets to become respondents (Informed Consent). Data collection was conducted through observations by researchers on respondents and conducting observations. Research with Parametric Test Paired Sample T-test obtained a p Value of (0.02) <α (0.05), so there is a significant effectiveness of red ginger compresses on reducing pain scales in the elderly, and can be used as an alternative to reduce pain scales.